Differential effect of metformin and/or glyburide on apelin serum levels in patients with type 2 diabetes mellitus: Concepts and clinical practice - Hayder M Al-Kuraishy; Ali I Al-Gareeb; Huda J Waheed; Thabat J Al-Maiahy (Wolters Kluwer Medknow Publications, 2018)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder associated with abundant adipocytokine changes which may play an important role in the progression of insulin resistance and micro- and macro-vascular complications. Therefore, the objective of this study was to assess the differential effect of metformin alone or in combination with glyburide on apelin serum levels in patients with T2DM. In this case-control study, fifty patients with T2DM in the age range of 45-65 years and twenty-five healthy controls matched for age and body weight were recruited from single endocrinology center, subdivided according to the diabetic pharmacotherapy into: Group I: healthy controls (n = 25), Group II: T2DM patients on metformin (n = 15), Group III: T2DM patients on glyburide (n = 17), and Group IV: T2DM patients on metformin plus glyburide (n = 28). Biochemical and anthropometric variables in relation to apelin serum levels were estimated. Apelin serum levels were low in normal healthy controls compared to T2DM patients (P < 0.01). The differential effect of diabetic pharmacotherapy on apelin serum level was statistically significant (P < 0.01) compared to the controls, but insignificant when compared among used drugs (P > 0.05). Apelin level was high in T2DM compared to the controls; both metformin and glyburide might play a role in this elevation.